The effect of accounting conservatism on the cost of equity capital -An experimental study on companies listed on the Damascus Stock Exchange- - محمد نذير (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The study aimed to determine the effect of accounting conservatism (measured by the ratio of the market value of equity to book value) on the cost of equity capital (measured according to the income model developed by Ohlson (1995)). To achieve that aim; Secondary data was collected from the annual financial reports of companies listed on the Damascus Stock Exchange, which are available on the official website of that market. The data was analyzed using the Eviews 10 program. The study also used time-sectional data, Panel Data. The number of these companies reached 19 during the period from 2016 to 2020, with a total of 95 views. The results showed that there was no significant effect of accounting conservatism on the cost of capital, whether before adjusting the size variable, or during its adjustment, while the results showed that controlling for the period in which the Corona epidemic appeared showed a direct effect with an explanatory power of 59.61%.